PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI KSP CU LESTARI WONOSOBO - Agustinus Aji Prastyanto, 0935020704 (Students Journal of Economic and Management, 2016)
This research is intended to discover the influences of work motivation, leadership and compensation on the employees performance in the credit union of "CU Lestari" Wonosobo. It worked on population and samples of 30-employees CU Lestari Wonosobo, with the measured variables including : work motivation, leadership, and compensation as a set of independent variables as well as employees performance as a dependent variable. The data was obtained by mean of questionnaires and analyzed with a double regression. The reasearch suggested that work motivation positively and significantly influences on the employees performance of CU Lestari Wonosobo. Work motivation resulted by appreciation, challenging job, persistence and ecouragement to gain achievement become the aspects of well-done assigments. Leadership, in the other hand, positively and significantly influences on the employees performance of CU Lestari. In the light of the employees preview, the leader in CU Lestari is capable for building up the natures of democratic leadership, such as being consultative, making collective decision, delegating assignment equitably and fairly, and so that this ecourages the employees to perform properly. Compensation positively and significantly influences on the employees performance of CU Lestari. Compensation in terms of salary, promotion and reward are the aspects of those encouraging work performance as well as maintaining employee loyalty. Work motivation, leadership and appreciation simultaneously influence on the employees performance in CU Lestari. The value of work motivation, leadership and compensation of the employees work performance reaches 83,7%. It is concluded that work motivation, leadership and compensation result in highly impacts on the work performance of CU Lestari. Key Words : Work motivation, leadership, compensation, performance